Utilization of Deconcentration Health Funds in Planning, Budgeting, and Implementation in Indonesia - Gurendro Putro1, Ristrini1, Tumaji1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Deconcentration funds are funds that given to regions in achieving the target echelon 1 indicator of the main units in the ministry of health with program performance indicators, then translated into echelon 2 targets with the achievement of activity performance indicators. This deconcentration fund is one for health financing in achieving the National Medium-Term Development Plan (RPJMN) in the health sector. Aim: to examine the allocation of deconcentrated funds in planning, implement, monitoring and evaluating. Method: the secondary data document was analyzed for the allocation of deconcentrated funds, from the center in each division of the program. This research was conducted for 4 months from September to December 2018. Result: the highest deconcentration funds from 2016 to 2017 were highest in the North Sulawesi provincial health department of 75.68% and 98.64%, while the lowest in the North Kalimantan provincial department was 39.25% and 68.03%. Whereas for 2018 the highest realiation was in the Southeast Sulawesi provincial health department at 97.36% and the lowest in the Aceh provincial health department was 72.86%. Conclusion: the deconcentration fund planning it is done top down and a menu of programs or activities has been determined. The amount of fund allocation has also been determined by the center, the regions only make and implement what has been made by the center. Activities in the area need to be monitored and evaluated both in substance and financial programs